Pembentukan Kelompok Peduli Penyakit Tidak Menular di Samigaluh, Kulon Progo - Tri Wulandari Kesetyaningsih; Sri Nabawiyati Nurul Makiyah; Tri Pitara Mahanggoro; Muhammad Afif Nadirrafi; Putra Alifa Zamzam; Intan Kusuma Ayu Setyaning Galih; Zannuba Aisyah Chapsoh; Devi Ardiyanti; Rizky Revinda Devi; Anggita Nur Cahya Willynia (Jurnal Surya Masyarakat, 2023)
Based on observations, information was obtained that the elderly hypertension rate was quite high (70%) in Ngaran II Hamlet. Some of the possible causes are the lack of knowledge and public awareness about non-communicable diseases (NCD), in addition to the lack of cadres and equipment. This causes the Posyandu not to run optimally. Integrated activities for field supervisors and students include forming a NCD care group. NCD prevention and screening training was given to members of the NCD Care group, with material on blood pressure checks, simple blood tests and determination of body mass index. At the beginning and end of the training, an evaluation was conducted to assess the level of knowledge of the participants. The NCD care group consists of 9 health cadres. The training methods include theory, discussion, and practice. Participants were aged between 36-54 years (43.6) with 55.56% high school education and 44.44% junior high school education. Of the 9 participants, only 7 completed the test. It can be seen that there is an increase in knowledge from the average pretest score of 45.54 to 68.75 post-test score. Statistical test using Paired T-test showed a significant increase (p 0.001). It was concluded that the training succeeded in significantly increasing knowledge about NCDs and their prevention